TINJAUAN KRIMINOLOGIS TERHADAP KEJAHATAN PEMBUNUHAN YANG DILAKUKAN OLEH PEREMPUAN - Muhammad Sabri (MITZAL (Demokrasi, Komunikasi dan Budaya) : Jurnal Ilmu Pemerintahan dan Ilmu Komunikasi, 2021)
This study aims to determine the criminological review of the crime of murder committed by women. This type of research uses a qualitative approach, namely understanding criminological actions against murder offenses committed by women. This research was conducted in three research locations, namely; (1) Sidrap District Court; (2) Sidrap Police Station; and (3) Sidrap Class II B Detention Center. In collecting data, the researcher used in-depth interview method where the researcher acted as the research instrument and supported by secondary data. The results showed that; (1) there are factors that cause the crime of murder committed by women in Sidrap Regency, namely; (a) internal factors, caused by the influence of age and psychology; and (b) external factors caused by the role of the victim and the family environment; and (2) the efforts made by law enforcement officers, in this case the Sidrap Police and their staff in tackling the crime of murder committed by women, are generally taken in 2 (two) ways, namely; (a) preventive measures (prevention); and (b) repressive efforts (eradication).